Lexicographic description of the old russian monthliy sticherarion of the 12th century - Malygina Mariia (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2012)
The article is dedicated to lexical features of the earliest text witnesses of Church Slavonic Monthly Sticheration of the 12th century. Numerous lexemes not attested in historical dictionaries of Slavic languages has been revealed and described in the article. Thanks to the observations of the earlier sources many words previously described in historical dictionaries has been dated to the earlier time. In this issue the second part of the paper is published; for the fi rst part see the previous issue.